The Influence of Urban and Rural Environments on Students' Entrepreneurial Intentions: A Conceptual Framework - Al Harrasi, Zahran Abdulwahad; Ali, Mass Hareeza (Advances in Social Sciences Research Journal, 2025)
This study provides a conceptual framework on the influence of urban/rural environments in shaping students' entrepreneurial intentions. Since entrepreneurship plays a crucial role in economic growth and development, it is important to understand the factors that affect individuals' intention to be entrepreneurs, especially at school age. A large proportion of research found that urban/rural environment was among the effective factors. Therefore, this study aims to present a conceptual framework on how urban and rural environments affect students' entrepreneurial intentions and therefore their decision to start their own business in the future. Therefore, this study assumes that students in urban areas are more exposed to economic and entrepreneurial activities than students in rural areas. Hence, it leads to a greater entrepreneurial intention with students living in those urban areas than those in rural areas. The study concludes with implications for policymakers and suggestions for further research.